Efeito da prometazina impregnada em cateter vesical de demora sobre biofilmes de bacilos Gram negativos associados à infecção do trato urinário - Gomes, Francisco Ivanilsom Firmiano (2023)
Urinary tract infection is one of the main complications related to health care, especially when it comes to the use of invasive medical devices. Indwelling bladder catheters are foreign bodies that are inserted into the urethra and made tolerant to bacterial colonization and biofilm development. Biofilms provide greater protection and bacterial resistance. Efflux pumps are important means of bacterial evasion of the action of antimicrobials and participate in the processes of formation and maintenance of bacterial biofilms, and can therefore be used to prevent the formation of bacterial biofilms. Thus, this study aimed to evaluate the inhibitory effect of a promethazine efflux pump impregnated in a catheter on the formation of biofilms by Gram-negative bacilli associated with urinary tract infection. 23 (5 Escherichia coli, 6 Klebsiella pneumoniae, 6 Proteus mirabilis and 6 Pseudomonas aeruginosa) isolates of Gram negative bacilli were used. The sensitivity of the isolates to promethazine was evaluated in planktonic and biofilm forms. The effect of the drug was evaluated in the concentrations referring to the minimum inhibitory concentration MIC, MIC/2 and MIC/4 on the formation of biofilms and in the concentrations referring to 2x minimum elimination concentration on the biofilm CEMB, CEMB and CEMB/2 on mature biofilms , using the biomass quantification technique. Furthermore, Foley catheter fragments were impregnated with promethazine 390 μg/mL and 3900 μg/mL to evaluate the effect of the drug on the formation of biofilms on the surface of the catheters, by counting colony forming units (CFU). Promethazine MICs ranged from 97.6 to 781.25 μg/mL and CEMBs ranged from 390.6 to 3125 μg/mL. Promethazine reduced (P<0.05) the biomass of biofilms in formation, in all concentrations tested, by 37.3%, 41.5% and 58.7%, from the lowest to the highest concentration. The impregnation of the catheters with promethazine at 390 μg/mL, in general, did not obtain significant results, however for the species of Escherichia coli and Proteus mirabilis the reduction in CFU's was 3 log. The impregnation of the catheters with 3900 μg/mL of promethazine significantly reduced the CFU's of the studied species, presenting significant results for all of them and, in general, the reduction of CFU's was greater than 5 log when compared to the control. When combined with antimicrobials, promethazine did not show a synergistic effect with antibiotics.